Reviewing the Role of the Endocannabinoid System in the Pathophysiology of Depression - Gallego-Landin, Ines; García-Baos, Alba; Castro-Zavala, Adriana; Valverde, Olga (Frontiers in Pharmacology, 2021)
Major depressive disorder is a high-impact, debilitating disease and it is currently considered the most prevalent mental illness. It is associated with disability, as well as increased morbidity and mortality. Despite its significant repercussions in our society, its exact pathophysiology remains unclear and therefore, available antidepressant treatment options are limited and, in some cases, ineffective. In the past years, research has focused on the development of a multifactorial theory of depression. Simultaneously, evidence supporting the role of the endocannabinoid system in the neurobiology of neuropsychiatric diseases has emerged. Studies have shown that the endocannabinoid system strongly impacts neurotransmission, and the neuroendocrine and neuroimmune systems, which are known to be dysfunctional in depressive patients. Accordingly, common antidepressants were shown to have a direct impact on the expression of cannabinoid receptors throughout the brain. Therefore, the relationship between the endocannabinoid system and major depressive disorder is worth consideration. Nevertheless, most studies focus on smaller pieces of what is undoubtedly a larger mosaic of interdependent processes. Therefore, the present review summarizes the existing literature regarding the role of the endocannabinoid system in depression aiming to integrate this information into a holistic picture for a better understanding of the relationship between the two.